Successful management of acquired left bronchial stenosis caused by massive atelectasis. (March 2019) - Miyahara, Jun; Ohhashi, Taku; Nakashima, Hideyuki; Sugiura, Hiroshi; Ohki, Shigeru
Acquired bronchial stenosis is rare in children, usually caused by infection or traumatic granuloma due to chronic intubation. A case of severe acquired left bronchial stenosis successfully treated by conservative management for gastroesophageal reflux and atelectasis is reported. A male infant born at 24 weeks' gestation, weighing 461 g, presented with massive atelectasis of the left lower lobe and severe left bronchial stenosis, based on chest computed tomography performed for the evaluation of respiratory failure at the age of 8 months. He responded well to the placement of a duodenal tube for gastroesophageal reflux and chest physiotherapy, reducing the symptoms of atelectasis and successfully managing the left bronchial stenosis. Acquired bronchial stenosis could be caused by bronchial shift due to atelectasis, and it can be cured by conservative management. In cases of acquired bronchial stenosis with massive atelectasis, it is important to consider atelectasis as a potential cause of the acquired bronchial stenosis.